Debt and fiscal responsibility in a federal structure: The case of Pakistan - Nadia Tahir; Pervez Tahir (Romanian Journal of Fiscal Policy (RJFP), 2012)
A recent amendment in Pakistan's federal constitution allows provinces to borrow domestically and abroad. There is a concern that it may generate unsustainable debt burden, considering the country's delinquent monetary policy and a historical deficit bias. The objective of this paper is to assess sustainability of public debt. First, we use Cecchetti, et al. (2010) methodology to regress public debt on indicators of fiscal stance i.e. primary deficit and structural deficit at federal level for the period 1976-2011. We conclude that fiscal stance remained opportunistically expansionary. Next, we look at debt sustainability and its implications for macroeconomic management at provincial level by separating the effects of growth and inflation on provincial public debt, interest payments, and primary balance by using the framework of Liu, et al. (2009). Our findings suggest declining debt sustainability at provincial level, which calls for a strong regulatory framework and coordination between federal and provincial debt strategies.
Keywords: E52; E58; E62; E63; H61; H62; H63; 330; Subnational finance; Fiscal responsibility; Monetary policy; Fiscal federalism; Pakistan